Analisis Sifat Fisika dan Kimia serta Kandungan Logam Sumber Air Panas di Provinsi Lampung - Rusyda Maulida Khairati; Rinawati Rinawati; Kharisma Citra Aprilia; Anisa Rahmawati; Nurhudawati Ningsih; Agung Abadi Kiswandono (Jurusan Kimia FMIPA Universitas Lampung, 2025)
Hot springs can be explored for geotourism activities. Geotourism is part of the main field in geology that can contribute to sustainable development. Therefore, hot springs are explored to determine their potential based on their physical and chemical properties. There were three places studied, namely Way Sulfur Kalianda baths, hot springs in Natar, and hot springs in Banjit, Way Kanan. The physical and chemical properties of hot springs measured in situ include total dissolved solids, dissolved oxygen, pH and temperature, while total metal concentrations are determined using ICP-AES. The measured pH value ranged from 5.2-8.1, the average measured temperature ranged from 37-52 °C. The highest and lowest DO values were 9.1 mg/L and 5.5 mg/L respectively. The average TDS and TSS values at the three sample locations were 3620 mg/L and 16.7 mg/L respectively. The highest concentrations of the metals Al, Ba, Cu, K, Ni, Pb are found in Natar, South Lampung, while the highest concentrations of B, Co, Li, Na are in Way Kanan, North Lampung. The highest concentrations of Mg, Mn, Ca are found in Way Sulfur, Kalianda, South Lampung. Concentrations of other metals were generally low and similar at the hot spring sample points studied. With the high content of harmless minerals in hot springs, hot springs can be explored for geotourism activities.